2010
DOI: 10.1080/17450390903478851
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study on the efficacy of paromomycin as a histomonostatic feed additive in turkey poults experimentally infected withHistomonas meleagridis

Abstract: Paromomycin is an aminoglycoside antibiotic with activity against protozoa. Currently, paromomycin is registered for food producing animal species. In a pilot study we evaluated the efficacy of different doses of paromomycin in the feed against Histomonas meleagridis in experimentally challenged turkey poults. Groups consisting of 30 birds each were given feed with 100, 200 and 400 ppm paromomycin, respectively, starting on day 1 through to day 42. One group of 30 birds was left untreated. On day 21 all birds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Histomoniasis in turkeys can be prevented by in-feed administration of paromomycin sulfate, an aminoglycoside antimicrobial agent (Lindquist, 1962;Bleyen et al, 2009;Hafez et al, 2010;van der Heijden et al, 2011). Maximum residue limits have been established according to the requirements of EC Council Regulation (EEC) 2377/90.…”
Section: Introductionmentioning
confidence: 98%
“…Histomoniasis in turkeys can be prevented by in-feed administration of paromomycin sulfate, an aminoglycoside antimicrobial agent (Lindquist, 1962;Bleyen et al, 2009;Hafez et al, 2010;van der Heijden et al, 2011). Maximum residue limits have been established according to the requirements of EC Council Regulation (EEC) 2377/90.…”
Section: Introductionmentioning
confidence: 98%
“…Several in vitro and in vivo experimental studies on chemotherapeutics have shown variable outcomes in finding a new and efficient therapy against H. meleagridis infections (Hu & McDougald, 2002;Hafez & Hauck, 2006;Bleyen et al, 2009;Hafez et al, 2010;Hauck et al, 2010b). Within recent years a trend towards non-chemotherapeutic alternative means has been set in the combat of histomonosis.…”
Section: Introductionmentioning
confidence: 99%
“…This stresses the need for new intervention strategies. Although in-feed paromomycin proved to be highly effective for the prevention of histomonosis (Bleyen et al, 2009;Hafez et al, 2010;van der Heijden et al, 2011), its registration may be difficult due to increasing concerns of consumers, scientists and legislators about (long-term) antibiotic usage and the development of resistance and its transfer to humans. Consequently, the quest for new intervention strategies has been focused on herbal products and probiotics due to a renewed interest in natural and herbal medicine.…”
Section: Introductionmentioning
confidence: 99%